2020
DOI: 10.3390/mi11040381
|View full text |Cite
|
Sign up to set email alerts
|

Drug Toxicity Evaluation Based on Organ-on-a-chip Technology: A Review

Abstract: Organ-on-a-chip academic research is in its blossom. Drug toxicity evaluation is a promising area in which organ-on-a-chip technology can apply. A unique advantage of organ-on-a-chip is the ability to integrate drug metabolism and drug toxic processes in a single device, which facilitates evaluation of toxicity of drug metabolites. Human organ-on-a-chip has been fabricated and used to assess drug toxicity with data correlation with the clinical trial. In this review, we introduced the microfluidic chip models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 146 publications
(142 reference statements)
0
70
0
2
Order By: Relevance
“…Organ-on-a-chip platforms can recapitulate the complexity of tissues and organs to some extent by combining cellular and extracellular cues in the chip. In addition to promising features such as providing tissue barriers and hydrodynamic forces that organ-on-a-chip devices offer, the inner surface of organ-on-a-chip devices can be coated with extracellular matrix (ECM) components to resemble the native cellular microenvironment and improve cellular adhesion [ 3 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Organ-on-a-chip platforms can recapitulate the complexity of tissues and organs to some extent by combining cellular and extracellular cues in the chip. In addition to promising features such as providing tissue barriers and hydrodynamic forces that organ-on-a-chip devices offer, the inner surface of organ-on-a-chip devices can be coated with extracellular matrix (ECM) components to resemble the native cellular microenvironment and improve cellular adhesion [ 3 , 5 , 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, rodents who got higher dosages of TZ (500 mg/kg) for 30 days exhibited rotations in learning and memory and declined cell reinforcement protections 10 . Besides, chronic administration of TZ (7.5 mg/kg) per diet for 90 days led to oxidative pressure and liver injury in grown-up rodents 3 .…”
mentioning
confidence: 98%
“…In the review of Chong and co-workers, it was demonstrated that the microfluidic chip models could be used to detect drug toxicity. Several biomarkers of toxicity were determined by organ-on-a-chip technology [ 81 ].…”
Section: Utilization Of Skin-on-a-chip Systemsmentioning
confidence: 99%